The Many Endings of Recent Epidemics: HIV/AIDS, Swine Flu 2009, and Policy - Berridge, Virginia (Centaurus, 2022)
Abstract Studying national and local contexts is essential for understanding the ending of epidemics and related policy responses. This article examines HIV/AIDS in the 1980s and 1990s and swine flu in 2009-2010 in the UK as comparative “tracer epidemics” to understand the multiplicity of endings from the perspective of the contemporary history of policy. Such endings can include: the political ending, changes in definition away from epidemic, the medical end, different endings for different “risk groups,” local endings, and media endings. This multiplicity of endings throws light on the nature of political and institutional structures and their change over time.